Identification of Plectosphaerella melonis from cucumber plants in Ukraine - KOPILOV, Evgeniy; TSEKHMISTER, Hanna; NADKERNYCHNA, Olena; KYSLYNSKA, Anna (Phytopathologia Mediterranea, 2021)
A fungus was isolated from diseased roots of Cucumis sativus grown in greenhouses. The morphological and cultural characteristics of the isolate allowed it to be classified as Plectosphaerella melonis. BLASTn analysis revealed 99% homology of the ITS sequence from the isolate with 14 Acremonium cucurbitacearum and P. melonis isolates, allowing attribution of the isolate to P. melonis (syn. A. cucurbitacearum). Koch’s hypothesis requirements were fulfilled for the isolate. Symptoms on host roots developed after 14 d of growing cucumber plants on infested soil. Plants of the cucumber variety Nizhynskyi 12 were very susceptible at the two leaf growth stage (2 weeks after sowing). Above-ground disease symptoms were absent after 14 d, even with severely diseased roots. This is the first report of P. melonis on C. sativus in Ukraine.